Immanuel in our place : seeing Christ in Israel's worship - Longman, Tremper (Phillipsburg, N.J. : P & R, 2001)
This book provides fascinating insights into the Old Testament tabernacle and temple, the priesthood, the sacrifices, and festivals. More than that, it shows how Jesus is the fulfillment of Old Testament sacred space, sacred acts, sacred persons, and sacred time. An aid to pastors, teachers, and laymen in teaching and reading the Old Testament, this work will enrich our understanding of Christ and deepen our worship.
Paradise gained and lost : sacred space from the beginning -- Altars : occasional testimonies to sacred space -- The tabernacle of Moses : sacred space for the long haul -- Solomon's Temple : sacred space settled in the land -- The furniture of the sanctuary : an inside look at sacred space -- The coming of Immanuel : where do Christians find holy space? -- The ʹolah : The whole burnt offering -- The minhah and shelamim : tribute and fellowship offerings -- The hattat and asham : sin and guilt offerings -- Christ : the once-and-for-all sacrifice! -- The rise of the priesthood -- Levites and the priestly life style -- Priestly service : God's bodyguards -- Jesus, the ultimate priest -- The Sabbath : the focus of sacred time -- Christ and Sabbath : sacred time reconfigured -- The haggim (pilgrimage festivals) : more on sacred time -- Festivals of Trumpets and the Day of Atonement : very special --Sacred times -- Purim : latecomer to sacred time.
Includes bibliographical references (p. 217-224) and index.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Relation to the Old Testament; Public worship in the Bible